PENERAPAN STRATEGI PEMBELAJARAN AKTIF (ACTIVE LEARNING) PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP PLUS CITRA MADINATUL ILMI BANJARBARU - Munawarah Munawarah; Saifuddin Saifuddin (ADDABANA: Jurnal Pendidikan Agama Islam, 2025)
Abstract:  This study discusses the "Implementation of Active Learning Strategies (Active Learning) in Islamic Religious Education Subjects at SMP Plus Citra Madinatul Ilmi Banjarbaru" with the background of active learning strategies because there are still students who are less focused on learning. Islamic religious education teachers not only have a function as teachers but are also able to make students interested in the lesson. The objectives of the study are: (1) to describe the Implementation of Active Learning Strategies (Active Learning) in Islamic Religious Education Subjects at SMP Plus Citra Madinatul Ilmi Banjarbaru; (2) to find out the supporting and inhibiting factors. Subjects in the study: Islamic Religious Education teachers at SMP Plus Citra Madinatul Ilmi Banjarbaru and students as research reinforcements. Objects in the study: active learning in Islamic Religious Education subjects at SMP Plus Citra Madinatul Ilmi Banjarbaru. Data collection using observation, interview, documentation techniques. Data processing using data collection, data classification, editing and data interpretation. Then analyzed descriptively qualitatively, for conclusions using the inductive method.Based on the results of the study, it is known that the Implementation of Active Learning Strategies for Islamic Religious Education at SMP Plus Citra Madinatul Ilmi Banjarbaru has several components, namely: Delivering teacher and student opinions, students responding to friends' opinions, finding learning resources, solving problems (discussion). Supporting factors are educators, students, and facilities and infrastructure. While the inhibiting factors are students, time factors and facilities and infrastructure. Keywords: Active Learning, Islamic Religious Education, Strategy.  Abstract: Penelitian ini membahas tentang “Penerapan Strategi Pembelajaran Aktif (Active learning) Pada Mata Pelajaran Pendidikan Agama Islam di SMP Plus Citra Madinatul Ilmi Banjarbaru” dilatar belakangi tentang strategi pembelajaran aktif karena masih ada siswa yang kurang fokus dalam pembelajaran. Guru pendidikan agama Islam selain memiliki fungsi sebagai pengajar tetapi juga mampu membuat ketertarikan siswa terhadap pelajaran. tujuan dari penelitian yaitu: (1) mendeskripsikan Penerapan Strategi Pembelajaran Aktif (Active Learning) pada Mata Pelajaran PAI di SMP Plus Citra Madinatul Ilmi Banjarbaru; (2) mengetahui faktor pendukung penghambatnya. Subjek dalam penelitian: guru PAI di SMP Plus Citra Madinatul Ilmi Banjarbaru dan siswa sebagai penguat penelitian. Objek dalam penelitian: pembelajaran aktif pada mata pelajaran PAI di SMP Plus Citra Madinatul Ilmi Banjarbaru. Penggalian data menggunakan teknik observasi, wawancara, dokumentasi. Pengolahan data menggunakan pengumpulan data, klasifikasi data, editing dan interpretasi data. Kemudian dianalisis secara deskriptif kualitatif, untuk kesimpulan menggunakan metode induktif. Berdasarkan hasil penelitian, diketahui bahwa Penerapan Strategi Pembelajaran Aktif PAI di SMP Plus Citra Madinatul Ilmi Banjarbaru ada beberapa komponen yaitu: Menyampaikan pendapat guru dan peserta didik, peserta didik menanggapi pendapat teman, menemukan sumber belajar, memecahkan masalah (diskusi). Faktor pendukung yaitu pendidik, peserta didik, dan sarana prasarana. Sedangkan faktor penghambat yaitu peserta didik, faktor waktu dan sarana prasarana. Kata Kunci: Pembelajaran Aktif, Pendidikan Agama Islam, Strategi.